Transforming Latin American food systems to build back better from COVID-19 and tackle climate change & nature loss - Castellanos, Andrea; Vertegaal, Doris M.; Bear, Anisa; Burian, Gabriela; Martínez Barón, Deissy; Dinesh, Dhanush (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Business as usual is no longer sustainable, particularly in the light of the pressures of Covid-19. Therefore, more synergy and public-private partnerships are key in order to create sustainable and resilient food systems in Latin America. Game-changing solutions are needed which should reach all stakeholders and deliver multifaceted benefits for society including healthier diets and reducing inequalities at the demographic level and in value chains. Innovation should be brought to scale in order to reach the SDGs. To empower actions at scale, place policies, regulations and incentives are needed which enable a sustainable recovery at the regional level. Innovative solutions and technical assistance should be able to reach farmers and be delivered in partnership with the private sector